Effects of in-service and coaching to increase teachers' use of research-based strategies in beginning reading. Issue 1 (2nd January 2020) - Goodnight, Crystalyn I.; Wood, Charles L.; Thompson, Julie L.
Abstract: In-service and coaching can increase teachers' use of research-based practices. This study examined the effects of in-service training plus coaching that included preconference, side-by-side coaching, and feedback on kindergarten teachers' use of research-based strategies during beginning reading instruction. Teachers were trained to enhance beginning reading instruction using research-based strategies including model-lead-test, unison responding (i.e., choral responding, response cards), and systematic error correction. Results indicated that for some teachers, a half-day in-service improved delivery of the research-based strategies, while others required side-by-side coaching to demonstrate improved use of the strategies. Teachers reported the in-service and coaching support were helpful and provided information on research-based strategies that increased student engagement. Implications for future research and practice are discussed.